Morphology and phylogeny of a new species, Uroleptus (Caudiholosticha) antarctica n. sp. (Ciliophora, Hypotricha) from Greenwich Island in Antarctica - Park, Kyung-Min; Min, Gi-Sik; Kim, Sanghee (Zootaxa, 2018)
This paper describes the morphological features based on standard methods and estimates their phylogenetic position using small subunit ribosomal RNA (SSU rRNA) sequences of a Uroleptus (Caudiholosticha) antarctica n. sp. population investigated from moss of the Greenwich Island, Antarctica. The morphology of Uroleptus (Caudiholosticha) antarctica n. sp. is characterized as follows: 213.0–238.0×67.5–74.5 μm size in vivo; contractile vacuole located slightly above left of mid-body; cortical granules lacking; three frontal and two frontoterminal cirri; five to six transverse cirri; one pretransverse cirri; one right and one left marginal rows; six to seven dorsal kineties; three caudal cirri.